Charge-discharge characteristics improvement through optimization of voltage range for LiNiCoMnO2 electrode for high energy density lithium-ion batteries - Puteh Melor Wesma Salehen; Halim Razali; Kamaruzzaman Sopian; Mohd Sukor Su’ait; Lee, Tian Khoon (Penerbit Universiti Kebangsaan Malaysia, 2018)
The development of suitable electrode materials for lithium ion batteries (LIBs) to enhance the performance of LIBs in order to meet increasingly demand globally is one of the challenges. Thus, for almost three decades since 1980, continuous study for high performance LIBs electrode has been done. In this report, the optimization charge-discharge characteristic of LiNiCoMnO2 (LNCM) cathode – layered structured material with lithium metal as anode has been evaluated. The electrode was assembled together with Celgard as separator and organic electrolyte Lithium hexafluorophosphate (1M LiPF6, EC:DEC 1:1) in coin cells (CR2032) under argon atmosphere inside a glove box. The charge-discharge performance test was conducted using Neware battery testing system. The discussion in this paper is focusing on the characteristic features of the charge-discharge profile, optimize charge-end voltage and rate capability (C-rate). The studies discovered the voltage range has been optimized up to 3.3-4.5 V at a constant current of 0.35 mA (0.1 C) with voltage plateau of 4.0 V. The result indicated the optimized range has the highest specific capacity of 118 mAh/g and most stable coulombic efficiency (94.3%).